SISTEM INFORMASI PENGOLAHAN DATA ABSENSI PEGAWAI KANTOR BALAI KB KECAMATAN PANYINGKIRAN BERBASIS WEB DAN ANDROID - Sujadi, Harun; Kusumadewi, Intan; Budiman; Alamsyah, Firhan Medina (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Employee absenteeism is a very important factor in a company or agency. The punctuality and integrity of employees who are assessed will help the development of the institution/institution. An attendance system that has up-to-date software is very important, because it has positive benefits for the institution or agency, especially interms of effectiveness, efficiency and speed. Along with that attendance is also not only done manually, but can help by using information technology. Attendance carried out at the Office of the KB Sub-District of Pengingkiran is still done manually, namely employees fill in attendance with signatures as well as the time of arrival and departure time. So, there are still a lot of problems when using the manual attendance system, such as not entering without information, coming and going home from the office not according to regulations, leaving the office during working hours and not knowing the leadership and there are still many problems caused. So that the KB Office of the Pengingkiran District requires an attendance application. With the application of the Employee Attendance Data Processing Information System, the Panyingkiran District Family Planning Office was able to overcome the occurrence of absenteeism violations in employees.